Fa’aliyyah Istikhdām Kitāb al-Lugah al-‘Arabiyyah al-Muṭawwar fi Ḍaui al-Takāmul baina al-‘Ilm wa al-Wahy bi Qism al-Riyāḍiyyāt wa al-‘Ulūm al-Ṭabī’iyyah bi Jāmi’ah Sunan Gunung Jati al-Islāmiyyah al-Hukūmiyyah Bandung - Siti Sanah; M. Abdul Hamid; Zulli Umri Siregar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The purpose of this study is to measure / test the effectiveness of the use of textbooks developed for Mathematics and Natural Sciences Department students to improve their academic achievement in Arabic subjects. This study used a quasi-experimental research method, namely giving treatment and measuring the consequences of the treatment. And how to obtain the data used in this study is a test (pretest and posttest). This trial was analyzed using the T and Anova test. The results of this study indicate that the average pre-test score of the Mathematika Education Students is 37.00 (low), the Physics Education Students are 32.31 (low); Chemistry Education is 33.17 (low) and Biology Education is 28.53 (low). For the average Postest Arabic Language Learning Outcomes for Mathematics Education Students of 79.74 (high); Physics education of 81.93 (high); Chemistry Education is 80.43 (high) and Biology Education is 81.72 (high). It can be seen that all student study programs have experienced a high increase in Arabic learning outcomes with an average increase of more than 0.70 (70%). The theoretical conclusion of this study is that the use of science-based textbooks that are integrated with the Al-quran verses for Islamic University students is very effective in increasing their academic achievement in Arabic courses.